Family Dynamics and Grandparents' Anxiety and Depression in Intergenerational Rearing Families: A Correlational Study - Yang, Chun-Yan; Xu, Hong-Jiao; Liu, Shan-Shan; Wu, Yue-Jing; Long, Yun; Liu, Hong-Sheng; Chen, Yao-Pian; Li, Xia (Frontiers in Psychiatry, 2021)
Backgrounds: In China, intergenerational rearing is a ubiquitous phenomenon based on the unique national conditions. The aim of the current study is to explore family dynamics in intergenerational rearing families as well as the correlation between family dynamics and anxiety-depression of grandparents in such families. Methods: The elderly bringing up grandchildren in intergenerational rearing families (n=141) and the elderly with no need for bringing up grandchildren (n=266) are investigated by use of following scales: general information questionnaire, self-rating scale of systemic family dynamics (SSFD), geriatric depression scale (GDS), self-rating anxiety scale (SAS). Results: (1) We scored from four dimensions (family atmosphere, the system logic, individuation and the concept of disease) in the structure of family dynamics. The comparison of dimensions scores (family atmosphere, the system logic, individuation and the concept of disease) of family dynamics , total scores of grandparents’ anxiety-depression in such two kinds of families is not statistically significant (p > 0.05). (2) In Pearson's correlation analysis, there is no significant correlation between the family atmosphere dimension in the family dynamic structure scale and total score of grandparents’ depression scale and the anxiety scale. The system logic dimension is negatively correlated with the scores of depression scale and anxiety scale. Individuation dimension is positively correlated with the scores of the anxiety scale. The disease concept dimension is positively correlated with the scores of depression scale and anxiety scale. Hence, the results are statistically significant. Conclusion: There is no significant difference in terms of family dynamics and risk of anxiety and depression among the grandparents between the two families. The system logic dimension, individuation dimension and disease concept dimension in family dynamic structure are correlated with the anxiety and depression of grandparents